Portal vein aneurysm-etiology, multimodal imaging and current management - Admir Kurtčehajić; Enver Zerem; Ervin Alibegović; Suad Kunosić; Ahmed Hujdurović; Jasmin Fejzic (2023)
Portal vein aneurysm (PVA) is a rare vascular abnormality, representing 3% of all venous aneurysms in the human body, and is not well understood. It can be congenital or acquired, located mainly at the level of confluence, main trunk, branches and bifurcation. A PVA as an abnormality of the portal venous system was first reported in 1956 by Barzilai and Kleckner. A review from 2015 entitled "Portal vein aneurysm: What to know" considered fewer than 200 cases. In the last seven years, there has been an increase in the number of PVAs diagnosed thanks to routine abdominal imaging. The aim of this review is to provide a comprehensive update of PVA, including aetiology, epidemiology, and clinical assessment, along with an evaluation of advanced multimodal imaging features of aneurysm and management approaches.